2021
DOI: 10.1139/cgj-2019-0711
|View full text |Cite
|
Sign up to set email alerts
|

Undrained triaxial tests on water-saturated methane hydrate–bearing clayey-silty sediments of the South China Sea

Abstract: Approximately 90% of gas hydrates are buried in fine-grained sediments on earth, especially in the South China Sea. The potential instability of the fine-grained sediments induced by hydrate dissociation requires us to investigate the shear strength and pore pressure response of the sediments during the hydrate recovery. To date, most of studies focused on the undrained mechanical behavior of gas hydrate-bearing sand or gas hydrate-free clay, and few studies examined gas hydrate-bearing fine-grained sediments.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
65
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 91 publications
(77 citation statements)
references
References 42 publications
8
65
0
Order By: Relevance
“…This is because the proportion of gas phase with lower thermal conductivity in pores gradually decreases. Moreover, the larger the particle sizes are, the higher the apparent thermal conductivity will be (7) As hydrate saturations increase, hydrate-bearing sediment's apparent electrical conductivity gradually decreases, while the resistivity index is opposite. 11 Geofluids…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is because the proportion of gas phase with lower thermal conductivity in pores gradually decreases. Moreover, the larger the particle sizes are, the higher the apparent thermal conductivity will be (7) As hydrate saturations increase, hydrate-bearing sediment's apparent electrical conductivity gradually decreases, while the resistivity index is opposite. 11 Geofluids…”
Section: Discussionmentioning
confidence: 99%
“…The physical characteristics of the hydrate-bearing sediment (HBS) are important to develop a reasonable exploitation plan [6,7], which mainly include the permeability [8], the thermal conductivity [9], and the electrical conductivity. In terms of HBSs' permeability research, Li et al [10] measured the permeability of unconsolidated quartz sands with different particle sizes before and after hydrate formation and found that the larger the particle sizes of the quartz sands, the higher the absolute permeability will be.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with the cementing hydrates, the pore-filling hydrates are believed to have a relatively small influence on the shear strength and stiffness of HBPM, but they can still restrict the movement of surrounding particles [37,39]; the loadbearing hydrates evolving from the pore-filling hydrates bond particles together into a cluster structure when hydrate saturation is beyond 40% [40]. In particular, the hydrate saturation can be higher than 80% in some local regions where the hydrates may directly bear loads [41,42]. Although hydrates with different pore-scale habits have different contributions to the shear strength and stiffness of HBPM, all of them can be regarded as a structure to bear and transfer loads.…”
Section: An Extended Three-phase Physicalmentioning
confidence: 99%
“…However, the hydrate reservoir existing in the excess gas is thought to have greater development potential since the free gas can be jointly exploited for increasing the natural gas production ( Yoneda et al., 2019 ). Generally, the current development of NGHs is in an important stage of progressing from field trials to commercial exploitation ( Wang et al., 2021 ; Zhou et al., 2018 ).…”
Section: Introductionmentioning
confidence: 99%